Clone, growth and stimulation : latex production factors - Gohet E; Clement A; Eschbach J M; Jacob J L; Prevot J C (Plantations, Recherche, Developpement, 1996)
Variations in tree growth, yields and physiological condition (in terms of latex sucrose and mineral P contents) of 5 Hevea clones (AF 261, AVROS 2037, PB 217, GT 1 and PB 235) under up to 78 stimulations per year (using Ethrel [ethephon]) were studied in a 7-year trial. The results indicated strong competition for assimilate distribution between growth and production and revealed the limits of effective stimulation for each clone. Beyond these clonal limits, serious malfunctioning occured. It was concluded that in order to be effective, stimulation must only be used if the clone typology and physiological condition of the latex-bearing tissue in the topped trees are precisely known.
Source Year: 1996
Keywords: Growth; Hevea brasiliensis; Hevea clones; Laticifers; Stimulation